Effects of Optimal Carbohydrase Mixtures on Nutrient Digestibility and Digestible Energy of Corn- and Wheat-Based Diets in Growing Pigs - Shunfen Zhang; Ruqing Zhong; Lixiang Gao; Zhengqun Liu; Liang Chen; Hongfu Zhang (Animals, 2020)
This study aimed to evaluate the effects of optimal carbohydrase mixture (OCM) on macronutrients and amino acid digestibility and the digestible energy (DE) in growing pigs fed the corn-soybean meal-based diet (CSM) and the wheat-soybean meal-based diet (WSM). A total of 36 ileal-cannulated pigs (50.9 ± 4.9 kg initial body weight) were allotted to four dietary treatments randomly, which included CSM and WSM diets, and two diets supplied with corresponding OCM. These OCMs were screened using an in vitro method from our previous study. After the five day adaptation period, fecal samples were collected from d six to seven, and ileal digesta samples were collected on d 8 and 10. Chromic oxide was added as an indigestible marker. The results show that the addition of OCM improved the apparent ileal digestibility (AID) of dry matter (DM), ash, carbohydrate (CHO), neutral detergent fiber, and gross energy (GE) and the apparent total tract digestibility (ATTD) of DM, CHO, and GE in CSM diet (p < 0.05), but reduced the apparent hindgut disappearance (AHD) of DM in CSM diet (p < 0.05). The ATTD of DM, crude protein (CP), ether extract (EE), ash, and GE and the AHD of DM, CP, EE, ash, CHO, and GE in WSM diet were improved by the OCM addition (p < 0.05), whereas the AID of DM, CP, ash, CHO, and GE were decreased (p < 0.05). The respective DE contents in CSM and WSM diets were increased from 15.45 to 15.74 MJ/kg and 15.03 to 15.49 MJ/kg under the effects of OCM (p < 0.05). Similar to the trend of AID of CP, the OCM addition increased the AID and standardized ileal digestibility (SID) of Ile, Thr, and Cys in CSM diet, but decreased the AID and SID of Ile, Phe, Thr, Val, Ala, Pro, Ser, and Tyr in WSM diet. In conclusion, the OCMs screened by an in vitro method could improve the total tract nutrient digestibility and DE for pigs fed corn-based diet or wheat-based diet but had inconsistent effects on the ileal digestibility of nutrients and energy.